AUTHENTICITY IN THE CONTEXT OF FOREIGN LANGUAGE LEARNING - Gülcan ÇAKIR (Fırat University, 2019)
This study examines the extent to which "authenticity" can be integrated into foreign language learning processes and to what extent the use of foreign language learning can be useful in foreign countries. The term "authenticity" suggests from the outset that something real or real will be included in the considerations. The approach is therefore seen as crucial by means of a textbook analysis, which relates to aspects of the current methodological-didactic discussion. It is assumed that a study-based analytical study is a sufficient instrument for gaining knowledge. Because the course book is usually equated with the learning process. Therefore, the teaching materials is examined "Wie bitte? (A.1.1 and A1.2)" and the authentic contexts present in the course books are demonstrated. Considering that foreign language teachers very often only use the teaching material in the classroom, the requirement to make the teaching material authentic is a necessity. The teaching process in a country where German is not spoken is unthinkable without taking into account the realities of the target language country. That is why the importance of authentic texts, pictures and speeches is very important. Real communication is possible through real communication. Likewise, one often learns to speak only through speech. Speak in dialogues that really exist or can exist. The authenticity principle is here a basis that offers the learner alternatives to produce realistic statements. Therefore, the importance of authentic texts, images and speech is of great importance in foreign language teaching.